[11C]K-2 image with positron emission tomography represents cell surface AMPA receptors. (December 2021) - Arisawa, Tetsu; Miyazaki, Tomoyuki; Ota, Wataru; Sano, Akane; Suyama, Kumiko; Takada, Yuuki; Takahashi, Takuya
Highlights: K-2OH, a major metabolite of K-2, does not penetrate cell membrane. K-2OH slowly passed through the blood brain barrier (BBB) with paracellular transport. Efflux of K-2OH from the brain is not a transporter-dependent. The amount of cell surface AMPAR positively correlates with that of total AMPAR. Abstract: The glutamate α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptors (AMPARs) is an important molecule in neurotransmission. We have recently developed the first positron emission tomography (PET) tracer [ 11 C]K-2 to visualize and quantify AMPARs in the living human brain. After injection, [ 11 C]K-2 is hydrolyzed at the terminal amide (and is thus metabolized to a major metabolite, [ 11 C]K-2OH ) within 10 min, representing the PET image in rodents and humans. Here, we found that K-2OH did not penetrate the cell membrane but slowly passed through the blood brain barrier (BBB) with paracellular transport. Furthermore, major efflux transporters in the BBB did not carry K-2OH . Logan graphical analysis exhibited reversible binding kinetics of this radiotracer in healthy individuals; these results demonstrated that the PET image of this tracer represents cell surface AMPARs with passive penetration of [ 11 C]K-2OH through the BBB, resulting in reversible binding kinetics. Thus, PET images with this tracer depict the physiologically crucial fraction of AMPARs.